Macrophages Are the Major Reservoir of Latent Murine Gammaherpesvirus 68 in Peritoneal Cells - Weck, Karen E. (American Society for Microbiology, 1999)
B cells have previously been identified as the major hematopoietic cell type harboring latent gammaherpesvirus 68 (γHV68) (N. P. Sunil-Chandra, S. Efstathiou, and A. A. Nash, J. Gen. Virol. 73:3275–3279, 1992). However, we have shown that γHV68 efficiently establishes latency in B-cell-deficient mice (K. E. Weck, M. L. Barkon, L. I. Yoo, S. H. Speck, and H. W. Virgin, J. Virol. 70:6775–6780, 1996), demonstrating that B cells are not required for γHV68 latency. To understand this dichotomy, we determined whether hematopoietic cell types, in addition to B cells, carry latent γHV68. We observed a high frequency of cells that reactivate latent γHV68 in peritoneal exudate cells (PECs) derived from both B-cell-deficient and normal C57BL/6 mice. PECs were composed primarily of macrophages in B-cell-deficient mice and of macrophages plus B cells in normal C57BL/6 mice. To determine which cells in PECs from C57BL/6 mice carry latent γHV68, we developed a limiting-dilution PCR assay to quantitate the frequency of cells carrying the γHV68 genome in fluorescence-activated cell sorter-purified cell populations. We also quantitated the contribution of individual cell populations to the total frequency of cells carrying latent γHV68. At early times after infection, the frequency of PECs that reactivated γHV68 correlated very closely with the frequency of PECs carrying the γHV68 genome, validating measurement of the frequency of viral-genome-positive cells as a measure of latency in this cell population. F4/80-positive macrophage-enriched, lymphocyte-depleted PECs harbored most of the γHV68 genome and efficiently reactivated γHV68, while CD19-positive, B-cell-enriched PECs harbored about a 10-fold lower frequency of γHV68 genome-positive cells. CD4-positive, T-cell-enriched PECs contained only a very low frequency of γHV68 genome-positive cells, consistent with previous analyses indicating that T cells are not a reservoir for γHV68 latency (N. P. Sunil-Chandra, S. Efstathiou, and A. A. Nash, J. Gen. Virol. 73:3275–3279, 1992). Since macrophages are bone marrow derived, we determined whether elicitation of a large inflammatory response in the peritoneum would recruit additional latent cells into the peritoneum. Thioglycolate inoculation increased the total number of PECs by about 20-fold but did not affect the frequency of cells that reactivate γHV68, consistent with a bone marrow reservoir for latent γHV68. These experiments demonstrate γHV68 latency in two different hematopoietic cell types, F4/80-positive macrophages and CD19-positive B cells, and argue for a bone marrow reservoir for latent γHV68.